Efficient production of clerodane and ent-kaurane diterpenes through truncated artificial pathways in Escherichia coli - Li, Fang-Ru; Lin, Xiaoxu; Yang, Qian; Tan, Ning-Hua; Dong, Liao-Bin (Beilstein Journal of Organic Chemistry, 2022)
The clerodane and ent-kaurane diterpenoids are two typical categories of diterpenoid natural products with complicated polycyclic carbon skeletons and significant pharmacological activities. Despite exciting advances in organic chemistry, access to these skeletons is still highly challenging. Using synthetic biology to engineer microbes provides an innovative alternative to bypass synthetic challenges. In this study, we constructed two truncated artificial pathways to efficiently produce terpentetriene and ent-kaurene, two representative clerodane and ent-kaurane diterpenes, in Escherichia coli. Both pathways depend on the exogenous addition of isoprenoid alcohol to reinforce the supply of IPP and DMAPP via two sequential phosphorylation reactions. Optimization of these constructs provided terpentetriene and ent-kaurene titers of 66 ± 4 mg/L and 113 ± 7 mg/L, respectively, in shake-flask fermentation. The truncated pathways to overproduce clerodane and ent-kaurane skeletons outlined here may provide an attractive route to prepare other privileged diterpene scaffolds.
Keywords: artificial pathway; ent-kaurene; Escherichia coli; overproduction; terpentetriene